The influence of pH on the structure and stability of the Grb2 dimer reveals changes in the inter-domain and molecular interaction: Could it be a modulation mechanism? - Tedesco, Jéssica A. [UNESP]; Dias, Raphael V.R. [UNESP]; Casteluci, Giovana [UNESP]; Pedro, Renan P. [UNESP]; de Oliveira, Leandro C. [UNESP]; Caruso, Ícaro P. [UNESP]; Melo, Fernando A. [UNESP] (Elsevier, 2023)
Cancer cells present an increased replicative potential as a hallmark. The increased replication leads to a higher intracellular pH. Grb2, an adapter protein, is mainly involved in several types of cancers due to its role in signaling pathways responsible for cell growth and proliferation. At pH 7, we observed a more compact structure, as seen by DLS and 1H NMR relaxation experiments, with high cooperativity within domains. On the other hand, we observed an increase in disordered structures at pH 8, with relative independence between domains characterized by higher melting temperatures and enthalpy of unfolding. CD and DLS corroborate with these observations at pH 8, conferring more flexibility among the domains, followed by lower unfolding cooperativity and increased hydrodynamic diameter at higher pH. In addition, 15N-HSQC chemical shift perturbations experiments showed significant differences in the positions of several amino acids spread on the Grb2 structure when pH was changed, which agrees with the previous results. Finally, the molecular dynamic analysis demonstrates that Grb2 presents a movement pattern where both SH3 domains move toward the center of the protein at pH 7. On the contrary, the pattern changes its direction at pH 8, where domains move outside the center of the protein, conferring a more elongated structure at higher pH. So, Grb2 presents significant structural and dynamic changes modulated by pH. If considering the role of Grb2 in cell signaling upstream, these conformational changes could be a critical mechanistic behavior of this protein, preventing/disrupting the stability of the cell signaling pathways related to cancer.
Keywords: Flexibility; Grb2; Inter-domain interaction; Molecular interaction; NMR; The influence of pH